Label‐free detection of immune complexes with myeloid cells. (12th May 2016) - Szittner, Z.; Bentlage, A. E. H.; Rovero, P.; Migliorini, P.; Lóránd, V.; Prechl, J.; Vidarsson, G.
Summary: The aim of this study was to provide proof‐of‐concept for quantitative and qualitative label‐free detection of immune complexes through myeloid cells with imaging surface plasmon resonance. Surface plasmon resonance imaging was first applied to monitor the binding of human sera from healthy and rheumatoid arthritis (RA) patients to immobilized citrullinated RA‐specific peptide antigens, histone citrullinated peptide 2 (HCP2) and viral citrullinated peptide 2 (VCP2). Next, the binding of monocytoid cell line U937 to the resulting immune complexes on the sensor surface was monitored. As control, binding of U937 was monitored to immunoglobulin (Ig)G subclasses simultaneously. Cell response results were compared to results of cyclic citrullinated peptide 2 (CCP2) enzyme‐linked immunosorbent assay (ELISA), clinical RA diagnosis and antigen‐specific antibody distribution of the samples. Human IgG3 triggered the most pronounced response, followed by IgG1 and IgG4, while IgG2 did not result in U937 cell binding. Serum samples obtained from RA patients resulted in a significantly increased cell response to VCP2 compared to healthy controls. The strength of cell response towards VCP2 immune complexes showed significant correlation with levels of antigen‐specific IgA, IgG and IgG3. Cellular responses on VCP2 immune complexes showed significant association with both CCP2‐based serological positivity and European League Against Rheumatism (EULAR) criteria‐based clinical RA diagnosis. Immunoglobulin‐triggered binding of monocytoid cells can be monitored using a label‐free multiplex technology. Because these binding events are presumably initiated by Fc receptors, the system provides a tool for biological detection of autoantibodies with diagnostic value, here exemplified by anti‐citrullinated antibodies. This provides added information to antibody levels, as interaction with Fc‐receptor‐expressing cells is also affected by post‐translational modification of the immunoglobulins.